Effect of Autoclave Cycles on Surface Characteristics of S-File Evaluated by Scanning Electron Microscopy - Razavian, Hamid; Iranmanesh, Pedram; Mojtahedi, Hamid; Nazeri, Rahman (Iranian Endodontic Journal, 2016)
Introduction: Presence of surface defects in endodontic instruments can lead to unwanted complications such as instrument fracture and incomplete preparation of the canal. The current study was conducted to evaluate the effect of autoclave cycles on surface characteristics of S-File by scanning electron microscopy (SEM). Methods and Materials: In this experimental study, 17 brand new S-Files (#30) were used. The surface characteristics of the files were examined in four steps (without autoclave, 1 autoclave cycle, 5 autoclave cycles and 10 autoclave cycles) by SEM under 200× and 1000× magnifications. Data were analyzed using the SPSS software and the paired sample t-test, independent sample t-test and multifactorial repeated measures ANOVA. The level of significance was set at 0.05. Results: New files had debris and pitting on their surfaces. When the autoclave cycles were increased, the mean of surface roughness also increased at both magnifications (P<0.05). Moreover, under 1000× magnification the multifactorial repeated measures ANOVA showed more surface roughness (P<0.001). Conclusion: Sterilization by autoclave increased the surface roughness of the files and this had was directly related to the number of autoclave cycles. Keywords: Autoclave; Endodontic Instruments; Root Canal Therapy; Scanning Electron Microscopy; Surface Characteristic